Studi Deskriptif mengenai Coping Stress pada Ibu yang Memiliki Anak dengan Autism Sebuah Penelitian di Sekolah â€œXâ€ Bandung - Erika Armajayanthi; Evany Victoriana; Kangga Liedia Ayu (Universitas Kristen Maranatha, 2017)
Having a child with autism can make a mother stress so that mothers need to relieve stress using coping stress. This study uses the theory of coping stress of Lazarus & Folkman (1984) to describe the coping stress used by mothers of children with autism in Schools